BCS Partner: Fujitsu maintaining corporate culture in a fast‐changing world. (19th June 2021) - Davis, Andrew; Hart, Sarah
Abstract: As COVID‐19 hit, Fujitsu embraced the opportunity of lockdown with characteristic positivity, showing its human‐centric nature by putting people at the centre of it all. Andrew Davis, Head of Future Workplace Strategy and Growth and Sarah Hart, Wellbeing Lead at Fujitsu Global Delivery, explain how the organisation did it.